A Status Report on Homeless Families in America's Cities - Waxman, Laura DeKoven; Reyes, Lilia M.; United States Conference of Mayors, Washington, DC. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1987)
This survey assesses the status of homelessness among families in cities. The data were collected from city officials during April 1987. The findings include the following: (1) the number of homeless families increased by 31 percent during the last two years; (2) families represented one-third of the homeless and a single parent headed two-thirds of those families; (3) the number of families temporarily living with friends or relatives has increased; (4) the most serious problem faced by the homeless was lack of food and/or poor nutrition; (5) the major consequence of homelessness was emotional and psychiatric problems; (6) a main cause of homelessness was lack of affordable housing; (7) the number of shelter beds in the survey cities had increased over the last two years; (8) families must break up in order to be accommodated in most shelters; (9) 30 percent of the families seeking emergency shelter were turned away; (10) use of the shelters during specific times of the day and the length of stay in the shelters were limited; (11) most cities provided assistance in obtaining permanent housing and emergency food assistance; (12) low-income housing was the service most lacking; (13) the number of homeless families was expected to increase; and (14) every city cited the lack of affordable housing as a major barrier to permanently housing families in the future. Statistical tables, a copy of the survey questionnaire responses, and comments from respondents are included. (FMW)
Microfiche.
Keywords: Emergency Programs; Reports, Research